1990
DOI: 10.1136/jcp.43.11.893
|View full text |Cite
|
Sign up to set email alerts
|

Cellular expression of lymphocyte function associated antigens and the intercellular adhesion molecule-1 in normal tissue.

Abstract: A detailed immunohistological analysis of normal tissues for the distribution of lymphocyte function-associated antigens (LFA) and the intercellular adhesion molecule-I (ICAM-1) showed several hitherto unrecognised patterns of LFA-3 and ICAM-1 expression. The widespread, but not ubiquitous, distribution of LFA-3 contrasted with the more restricted distribution of ICAM-1. Among epithelial cells, all tissues which were ICAM-1 positive were also LFA-3 positive with the single exception that thymic cortical epithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0
1

Year Published

1993
1993
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(41 citation statements)
references
References 21 publications
1
39
0
1
Order By: Relevance
“…Immunohistochemical studies have shown that the distribution of CD54 on normal human tissues is restricted. 40 In vivo administration of another anti-CD54 antibody into cynomologous monkeys prolonged renal allograft survival without damaging normal tissues. 41 Moreover, clinical trials in patients treated with another anti-CD54 antibody for the prevention of kidney allograft rejection 42 or the treatment of rheumatoid arthritis 43 have demonstrated that anti-CD54 is safe and has no overt toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical studies have shown that the distribution of CD54 on normal human tissues is restricted. 40 In vivo administration of another anti-CD54 antibody into cynomologous monkeys prolonged renal allograft survival without damaging normal tissues. 41 Moreover, clinical trials in patients treated with another anti-CD54 antibody for the prevention of kidney allograft rejection 42 or the treatment of rheumatoid arthritis 43 have demonstrated that anti-CD54 is safe and has no overt toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…VCAM-1, whilst largely present on activated endothelial cells, is also present on dendritic cells, neuronal cells and renal parietal epithelium (Rice et al, 1991), and in lymphoid malignancies shows a similar pattern of expression to that of E-selectin (Ruco et al, 1992). ICAM-1, which is elevated to a greater extent and in a greater proportion of these cancer patients, has a much wider cellular distribution (Smith & Thomas, 1990) and in addition to endothelial cells has been described on normal and malignant epithelial tissue including melanoma cell lines and primary tissue, renal cell lines and intestinal cell lines (Natali et al, 1990;Tomita et al, 1990;Becker et al, 1991). Thus at least some of the soluble ICAM-1 present in sera of cancer patients is probably derived from tumour tissue.…”
Section: Sera and Patientsmentioning
confidence: 99%
“…ICAM-1, the inducible ligand for lymphocyte function associated antigen-I (LFA-1) and Mac-i, is found on endothelial cells, leukocytes and some epithelial tissue (Smith & Thomas, 1990), and plays a major role in cell-cell interactions in inflammatory and immune responses. It has also been implicated in the progression of melanoma (Natali et al, 1990).…”
mentioning
confidence: 99%
“…Cytocentrifuge preparations of cell lines were air-dried (30 to 60 rain; 22 °C) fixed in cold (4 °C) acetone for 5 rain and examined immunocytochemically by the peroxidase-anti-peroxidase (PAP) method (Smith & Thomas, 1990). MAbs were used to define the following cellular antigens: vimentin (V9, Dako); CD23 (MHM6 from A. McMichael, University of Oxford, U.K.); CD21 (HB5, Becton Dickinson); CD30 (BerH2, Dako); CD39 (AC2, Serotec); C D l l a [leukocyte function antigen (LFA)-I, MHM24 from A. McMichael]; CD54 (intercellular adhesion molecule (ICAM)-I; RRI/1) and CD58 (LFA-3, TS2/9) (both from T. Springer, Harvard Medical School, U.S.A.); CD77 (BL antigen from J. Wiels, Institut Gustav Roussy, France); and CD10 (J5, Orthomune).…”
Section: E T H O D Smentioning
confidence: 99%